Two Type VI Secretion DNase Effectors are Utilized for Interbacterial Competition in the Fish Pathogen Pseudomonas plecoglossicida - Li, Yanyan; Yan, Xiaojun; Tao, Zhen (Frontiers in Microbiology, 2022)
Pseudomonas plecoglossicida is a facultative fish pathogen that possesses three distinct type VI secretion systems (named T6SS-1, -2 and -3). Our previous work indicated that only T6SS-2 of P. plecoglossicida mediates interbacterial competition. However, the antibacterial T6SS effectors and their functions are unclear. Here, we reported two T6SS effectors that mediate antibacterial activity. We first identified four putative antibacterial effectors (denoted as Txe1, Txe2, Txe3 and Txe4) and their cognate immunity proteins in three different vgrG clusters encoded by P. plecoglossicida strain XSDHY-P. Here, we showed that the growth of Escherichia coli cells expressing Txe1, Txe2, and Txe4 was inhibited, and these three effectors exhibited nuclease activity in vivo. The interbacterial competition assays with single- or multi-effector deletion mutants as attackers revealed that Txe1 was the predominant T6SS toxin of P. plecoglossicida strain XSDHY-P mediating the interbacterial killing. This work contributes to our understanding of bacterial effectors involved in the interbacterial competition.